DETERMINAN KINERJA ANGGARAN BELANJA PENDIDIKAN PADA KABUPATEN/KOTA DI ACEH - Syukriy Abdullah; Mulia Saputra; Dara Fazella; Hasnawati Hasnawati; Aulia Afridzal (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The purpose of this research is to examine the determinants of the Education Budget Performance in Aceh, namely Local Financial Independence, Last Year Budget Balance, Government Size, and Local Revenue Growth using data from districts and cities in Aceh for year 2011-2015. The results of the study show that Local Financial Independence and Last Year Budget Balance has a negative effect on Education Budget Performance, while the other two variables have no effect.